One-year Observation of Safety of Implantable Collamer Lens V4c Implantation Without Using an Ophthalmic Viscosurgical Device - Chen, Zhuoyi; Niu, Lingling; Zhao, Jing; Yao, Peijun; Wang, Xiaoying; Zhou, Xingtao (Frontiers in Medicine, 2022)
PURPOSE: To investigate the feasibility and safety of the implantable collamer lens V4c (ICL V4c) implantation without using an ophthalmic viscosurgical device (OVD-free technique). METHODS: This prospective consecutive case study enrolled 118 eyes of 60 patients (15 eyes were of male patients, 103 eyes were of female patients, age 26.19±5.03 years, spherical equivalent -10.05±2.73 D). Eyes were considered for OVD-free or OVD-using ICL V4c implantation based on the maintenance of the anterior segment during the surgery. The follow-up lasted for 12 months. The main measurements were visual acuity and changes in endothelial cell density (ECD) at 12 months. RESULTS: A total of 75 eyes were included in the OVD-free group and 43 in the OVD group. No infection or other complications were observed in any eye. In the OVD-free group, the safety and efficacy indices were 1.19±0.15 and 1.05±0.20, respectively. 74.5% of the eyes gained one or two lines of corrected distance visual acuity (CDVA), and 25.5% were stable. In the OVD group, the safety and efficacy indices were 1.17±0.17 and 1.03±0.15 respectively; 65.7% of the eyes gained one or two lines of CDVA, and 34.3% were stable. The mean change of ECD was 65.34 cell/ mm2 compared to the baseline in the OVD-free group and 25.94 cell/ mm2 compared to baseline in the OVD group (P = 0.038). CONCLUSIONS: The ICL V4c implantation with an OVD-free technique is a safe and feasible method in eyes with good maintenance of the anterior segment.